If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -112 = -27 + -5x Solving -112 = -27 + -5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '5x' to each side of the equation. -112 + 5x = -27 + -5x + 5x Combine like terms: -5x + 5x = 0 -112 + 5x = -27 + 0 -112 + 5x = -27 Add '112' to each side of the equation. -112 + 112 + 5x = -27 + 112 Combine like terms: -112 + 112 = 0 0 + 5x = -27 + 112 5x = -27 + 112 Combine like terms: -27 + 112 = 85 5x = 85 Divide each side by '5'. x = 17 Simplifying x = 17
| -4(6a-2)= | | 90(x+24)+90(x)=4x(x+4) | | 14.5y=6 | | 21nx-3=0 | | 7a+2=5a+3 | | 7x-10=3(x-2)+5(x-1) | | 95=-47-4(t+6) | | -2x+9y=-6 | | 10-6x-9x+3= | | 8(2c+2)= | | 27(x-1)=3(2x) | | 8y+56=15y | | 20-2v=3v | | 90(x+4)+15(x)=4x(x+4) | | 30+x=7x | | 3y=-15x+270 | | -38+8x=2(8x+1)+8 | | t=0.25(i-32720)+4867.5 | | 4x^2-89x-360=0 | | 6v-5v=3v+8 | | V^2-121=0 | | x+1+x+9=50 | | 36+7v=13v | | 10x-5y+6=6 | | 3(1+6m)=-16-m | | 0.03-0.4x=1.85 | | 7-3(9-x)=16 | | 2(a+6)=5+9 | | 3n^3+10n+16=8 | | 2z^2+5z+3= | | 2b+8(2b-3)=-3(-5b-6) | | -n-21=3(6n-7) |